Afeto na educação infantil: um estudo bibliográfico - Silva, Flávia Mello da (Universidade Federal de São Carlos, 2023)
The present undergraduate thesis aims to analyze and comprehend the impact of emotional education on the academic development of children in early childhood education. To carry out this work, bibliographic research was conducted online using the Scientific Electronic Library Online (SciELO), the Portal of Capes Journals, and Google Scholar, in order to find articles whose purpose was to present different perspectives on the topic to enable a proper analysis. The work begins with an introduction to the meaning of "affection" and an explanation of what early childhood education is. From this point, it proceeds to analyze the results of what was found during the research conducted from 2013 to 2022 and then concludes with what was understood based on the findings. The results indicate that affection in early childhood education is extremely important, as it is through it that the child can develop pedagogically and feel more secure as an evolving individual.
Affection in early childhood education: a bibliographic study
Keywords: Educação infantil; Afeto; crianças; Child education; Affection; children; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO